Ethnobotanical Study of Plant Utilization in the Balinese Hindu (Metatah) Ceremony in Baubau - Supreni, Ni Made; Jumiati, Jumiati; Andarias, S. Hafidhawati (Jurnal Biologi Tropis, 2026)
The use of plants in traditional societies is not only utilitarian but also plays an important role in cultural practices and religious ceremonies as part of an ethnobotanical knowledge system rich in symbolic meanings. This study aimed to identify plant species used, describe the plant parts utilized, and reveal their symbolic meanings in the Metatah (tooth-filing) ceremony among Balinese Hindu communities in Ngkaring Karing Village, Baubau. A descriptive qualitative approach was applied using purposive sampling involving tokoh adat (traditional leaders with knowledge of symbolic meanings), pemangku (Hindu religious leaders responsible for ritual practices), and serati (ceremony specialists responsible for preparing ceremonial materials, particularly plant materials). Data were collected through direct observation, semi-structured interviews, and documentation. The results showed that 38 plant species were used in the Metatah ceremony without substitution, indicating strong consistency in cultural values and knowledge transmission. The plant parts utilized included leaves, flowers, fruits, seeds, stems, and rhizomes. Each plant carries symbolic meanings related to purity, life, prosperity, spiritual cleansing, protection, balance, harmony, and the relationship between humans, nature, and the spiritual realm. This study concludes that plant utilization in the Metatah ceremony is deeply embedded in cultural and symbolic systems, reflecting the continuity of local ethnobotanical knowledge within Balinese Hindu communities in diaspora and contributing to its documentation and preservation.